Integrasi Tasawuf dan Psikoterapi Islam: Tinjauan Literatur tentang Pengaruh Spiritualitas dan Kesehatan Mental - Mursalin, Hisan (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
In this complex era, psychological and emotional challenges are increasing. Psychotherapy has become a commonly used way to help individuals overcome these problems, but in a society that leans more toward a secular outlook, the spiritual aspect is often overlooked. So it is necessary to know the principles of Sufism from an Islamic perspective in the practice of psychotherapy, with the hope of improving the mental well-being of Muslim individuals. This research aims to explore the implementation of an integrative approach between Sufism and psychotherapy in the context of understanding Islamic values ​​in order to improve the mental well-being of Muslim individuals. Apart from that, the aim of this research is to examine the main objectives of Sufism which is based on the Koran and Sunnah. This research applies qualitative methods using a literature study approach and descriptive analysis techniques. Mental and mental disorders are often caused by being too attached to the material world, and the Koran recommends that Muslims always remember Allah to achieve peace of mind. The Koran is an effective way to heal sick souls and mental disorders. Sufism as a form of spiritual medicine in Islam, is seen as a way to overcome mental and mental disorders. Even though Sufism is not included in the official teachings of Ahlu Sunnah Wal Jamaah, it is still considered part of Islam and uses the Al-Quran and As-Sunnah as references in treatment.